Deep Understanding about Strategies for Self-resilience of Newly Appointed Nurses; Qualitative Approach (International Journal of Nursing Education, 2020)
The purpose of this study was to examined existing strategies for self- resilience of newly appointed nursesin National Hospital of Sri Lanka. Authors studied physical, psychological and socio-cultural strategies forself-resilience of newly appointed nurses. The target population of this study was eleven months experiencesin various clinical settings in National Hospital of Sri Lanka and number of samples was fifteen. Nurseswere selected using purposive sampling method as qualitative study. The data were collected from Januaryto August 2019. According to this study, result outcomes were taken from the fifteen interviews and thosefindings categorized into three main themes. Some special findings were presented as quotations. Thosethemes were a) happy and strong mind, b) pretty and healthy life and c) good and loving social bondfor enhancing self-resilience. These findings suggest to future generation of nursing profession to increasetheir self-resilience. Additionally, nurses and nursing administrators learning how to enhance and improveresilience while working in the profession of nursing.